Kreacje męskich bohaterów w powieści Fizyka smutku Georgiego Gospodinowa - Puzio, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The subject of the paper will be to discuss the creation of the main character of the novel Physics of Sorrow by Georgi Gospodinov, who – because of the ability to impersonate various beings – sees through the eyes of others, hears sounds that reach his ears, sympathizes with their fear, sadness, joy. The analysis and interpretation of the Bulgarian novelist’s work will focus on male characters: the boy, and also the Minotaur imprisoned and their emotional world. An important place in the novel is occupied by the space of the labyrinth, organizing the narrative, both in the context of weaving individual threads and constructing a hybrid, fragmentary text. The work is full of self-referential threads (there are many reflections related to writing and the idea that only what is written can survive) and autobiographical threads which lead to perceiving the evoked space of the labyrinth as a consistently developed artistic strategy.
The creations of male characters in the novel The Physics of Sorrow by Georgi Gospodinov
Keywords: Minotaur; masculinity; loneliness; labyrinth